Effect of Sample-Build Orientation on the Tensile Deformation and Properties of Ti6Al4V Processed by Laser Powder Bed Fusion - Sun, Shoujin; Zhang, Duyao; Palanisamy, Suresh; Liu, Qianchu; Schmidt, Michael; Dargusch, Matthew S. (Advanced Engineering Materials, 2024)
The effect of sample-build orientation on the tensile properties and deformation behavior of Ti6Al4V fabricated by laser powder bed fusion (LPBF) has been investigated by examining the changes in X-ray diffraction spectra, microstructure, and dimension on the longitudinal cross-sections after fracture. The anisotropy in strength is dominated by the difference in martensite (α′) lattice distortion, and the highest strength is achieved in the diagonally built sample (Z45) due to its largest α′ lattice distortion. The plastic deformation is mainly accommodated by sliding and micro-void formation between α′ laths due to the insufficient number of slip systems in hexagonal close-packed α′ phase. Therefore, the spatial orientation of α′ laths with respect to the loading direction is critical to the ductility. Different deformation mechanisms have been observed in different prior-β grains due to their different α′ crystallographic orientations. The highest elongation is achieved in the vertically built sample (Z) because α′ laths in the vertically built sample are spatially at ±45° with the loading axis.
CRIS-Team Scopus Importer:2024-10-25
Keywords: anisotropy; build orientation; laser powder bed fusion; mechanical property; Ti6Al4V